Pengaruh Kemanfaatan dan Kemudahan Penggunaan terhadap Kinerja Pegawai yang Dimediasi Kepuasan Pelanggan di Direktorat Lalu Lintas dan Angkutan Laut - Heri Susanto; Juneiro Marudut Halomoan Bakkara; Markus Yando Manurung; Abdul Rachman (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation in public services demands the implementation of technology that is not only functional but also capable of meeting user expectations. This study aims to analyze the influence of perceived usefulness and ease of use of the Marine Traffic and Transportation Management Information System application on employee performance at the Directorate of Marine Traffic and Transportation, as well as to examine the mediating role of customer satisfaction in this relationship. This research employs a quantitative approach using a survey method through questionnaires distributed to 152 application users from marine transportation companies. The data were analyzed using Structural Equation Modeling with a Partial Least Squares approach. The analysis results show that perceived usefulness and ease of use have a positive and significant effect on customer satisfaction. Furthermore, both variables, along with customer satisfaction, were also found to have a significant direct effect on employee performance. More importantly, customer satisfaction significantly mediates the relationship between perceived usefulness and ease of use and employee performance. These findings underscore that improving user experience quality by creating applications that are useful and easy to operate is a crucial strategy for building customer satisfaction, which ultimately has implications for enhancing public service employees’ performance perceptions.